Mesozooplankton of the Emboraí Velho River estuary, Northern Brazil - Fernandes, Farley Darlan dos Santos; Silva, Brenda Ribeiro Padilha da; Pinheiro, João Victor de Moraes Souza; Queiroz, Jislene Brito Matos; Pereira, Luci Cajueiro Carneiro; Costa, Rauquírio Marinho da (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2023)
This study investigated the spatio-temporal variations of mesozooplankton from the estuary of the River Emboraí Velho River (Northern Brazil). Samplings were performed at two fixed stations in January, April, August and November 2018, and April, September and December 2019. Zooplankton samples were obtained through horizontal trawls carried out with plankton nets. Hydrological variables and chlorophyll-a concentrations were simultaneously measured. High temperatures (29.06 ± 0.16 °C) were observed in December/2019 (E1), turbidity (134.50 ± 80.00 NTU) in April/2019 (E2), dissolved oxygen concentrations (6.00 ± 0.98 mg.L-1) in August/2018 (E2), and chlorophyll-a concentrations (15.04 ± 6.21 mg.m-3) in January/2018 (E1). Pseudodiaptomus richardi (1,097.31 ± 1,903.50 ind.m-3) showed the highest abundances at station-E2, in April/2019. Copepodites of Acartia (15,481.49 ± 45,094.33 ind.m-3) and Pseudodiaptomus (830.22 ± 1,588.92 ind.m-3) showed higher abundances in April/2019 (E2). High Abundances of Oikopleura dioica (1,349.81 ± 115.50 ind.m-3; E1) and Gastropoda larvae (3,822.92 ± 10,853.39 ind.m-3; E2), in turn, occurred in January/2018 and April/2019, respectively. Acartia lilljeborgii and Euterpina acutifrons also showed high abundance values, both in November/2018 (E1). The structure and dynamics of the mesozooplanktonic community in the estuary of the River Emboraí River presented spatial and temporal variations, which were influenced by precipitation and local fluctuations in salinity.